Kajian Stilistika pada Lagu-lagu Band Ungu - Abdulloh Abdulloh; Fransisca S.O. Dedi; Ina Lusiana (LPPM STKIP PGRI Bandar Lampung, 2023)
This study aims to analyze the stylistic form of the lyrics of song describing Ungu with purple song entitled Ungu Melayang, Berikan Aku Cinta, Tercipta Untukku, and Kekasih Gelapku. The method use in this study is descritive of this kualitatif. This study clearly describe or illustrate the style of language and detail about the collection of songs Ungu. Sources of in this study is a song titled Ungu Melayang, Berikan Aku Cinta, Tercipta Untukku, and Kekasih Gelapku. The results of this study concluded that the song is not only dominated by Ungu style personification, hyperbole, and assonance but also redundancy, climax, inversion, and a pars pro toto sinekdoke. Writing songs more Ungu band using style as party of the expression of feelings and pored in poetry writing. The uniqueness of the lyrycs the songs that is Ungu in addition to using a lot of style, the lyrics are melancholy was also if sung by a singer.